Fluopyram activates systemic resistance in soybean - Rocha, Leonardo F.; Subedi, Arjun; Pimentel, Mirian F.; Bond, Jason P.; Fakhoury, Ahmad M. (Frontiers in Plant Science, 2022)
The soybean cyst nematode (SCN) (Heterodera glycines Ichinohe) is a significant yield-limiting factor in soybean production in the Midwestern US. Several management practices are implemented to mitigate yield losses caused by SCN, including using SDHI (succinate dehydrogenase inhibitors) fungicides delivered as seed treatments. A set of studies were conducted to evaluate the effect of two seed-applied succinate dehydrogenase inhibitors (SDHI) compounds, fluopyram and pydiflumetofen, on SCN population densities, plant injury, and plant growth. Cyst counts in untreated control and pydiflumetofen treated plants were 3.44 and 3.59 times higher than fluopyram, respectively, while egg counts were 8.25 and 7.06 times higher in control and pydiflumetofen. Next-generation sequencing was later employed to identify transcriptomic shifts in gene expression profiles in fluopyram and pydiflumetofen -treated seedlings. RNA expression patterns of seed treatments clustered by sampling time (5 DAP vs. 10 DAP); therefore, downstream analysis was conducted by timepoint. At 5 DAP, 10,870 and 325 differentially expressed genes (DEG) were identified in fluopyram and pydiflumetofen, respectively. These same treatments generated 219 and 2 DEGs at 10 DAP. Multiple DEGs identified in soybean seedlings treated with fluopyram are reported to be linked to systemic resistance, suggesting a potential role of systemic resistance in the suppression of SCN by fluopyram, in addition to the known nematicidal activity. The non-target inhibition of soybean succinate dehydrogenase genes by fluopyram may be the origin of the phytotoxicity symptoms observed and potentially the source of the systemic resistance activation reported in the current study. This work helps to elucidate the mechanisms of suppression of SCN by fluopyram.